Efektivitas Media Pembelajaran Pop-Up Book terhadap Hasil Belajar Siswa Kelas V SDN 106811 Bandar Setia - Siregar, Indah Amaliyah (Al-DYAS, 2025)
The low learning outcomes in Indonesian language among fifth-grade students at SDN 106811 Bandar Setia were identified as a major issue through preliminary observations, which revealed a monotonous learning process, limited media innovation, and minimal active student engagement. This study aims to examine the effectiveness of pop-up book media in improving student learning outcomes on the topic “Facts and Opinions in Advertisements.” Employing a quantitative approach with a one-group pretest-posttest design, the study involved 28 purposively selected students. Instruments included multiple-choice tests to assess learning outcomes before and after instruction, as well as a practicality questionnaire for the media. Data were analyzed using mastery percentage, N-Gain calculations, and descriptive analysis. The results showed an increase in the average score from 58 (pretest) to 88 (posttest), with learning mastery rising from 14% to 100%. An N-Gain score of 0.73 indicated a high level of effectiveness. Additionally, the media’s practicality was rated as excellent by both teachers (94%) and students (90%). In conclusion, pop-up book media is both effective and practical in supporting Indonesian language instruction and contributes significantly to enhancing student learning outcomes at the elementary level.